An Intelligent model of FAN automation for smart house - Saha, Subir; Imtiaz, Md. Niaz; Ali, Md. Akkas (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Embedded system use in smart house is very common now-a-days. Electrical device like TV, Computer, Mobile, Fan e.t.c. are very common for day to day life of everyone. These sorts of device are controlled manually by man or by remote control with different controller or different switch. As we are being more digitalized day by day and getting rid of any sorts of manual devices then we are more inclined to the digital controlling system. Developing countries are radically using this type of systems in a very large scale. We develop a system model that will help the developing smart house smarter. Our developed system works with the current electrical system. We developed the system that works automatically with the increase or decrease of temperature. If the temperature goes to 37° or more the fan runs with full speed the fan also run slower/faster when the temperature goes down/increase in every 2° and vice-versa. When the temperature is ≤ 20° it’s automatically stops. It can also operate manually though it has a switch connected to motor.